Pondok Pesantren dan Tantangan: Menyiapkan Santri Tangguh di Era Society - Karimah, Ummah; Mutiara, Diah; Rizki, Rizki; Farhan, Muhammad (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2023)
Pondok pesantren as an Islamic educational institution has presented the challenges of the era of society experiencing changes in the times and the character of the generation that lives in the present. Islamic boarding schools to be able to prepare students to be mentally hardiness and easier are not only capable in the religious (religious) field, but also must be able to overcome and deal with current societal turmoil, meaning that they excel in the fields of science and technology and remain superior in the field of religion. The purpose of this research is to find out the Islamic boarding school of SMA Ali Maksum Yogyakarta in preparing students as alpha generation who are hardiness and challenge the world of Islamic society education. This writing uses a descriptive-qualitative method with the type of research narrative research, for data collection is done by the process of interviews, observation, and documentation at the Pondok Pondok pesantren Ali Maksum Senior High School Yogyakarta. Technical analysis of data is carried out using the Miles and Hubberman model, namely by reducing, displaying and verifying data. The results of this study indicate that the Ali Maksum Islamic Boarding School has prepared various strategies in dealing with the times in society such as carrying out curriculum transformation through the school's mission, forming people who have strong faith, taqwa who are kaafa, have noble character, mastering science and technology that is mashlahah, technology information, and professional charity. Development of technology-based facilities and infrastructure, establishing cooperation between educational institutions, character building and developing life skills, leadership and entrepreneurship for the students of SMA Ali Maksum Yogyakarta as well as through a program of assistance services provided to prepare strong students.